Cultural Syndromes in a Changing World: A Longitudinal Investigation of Brazilian Jeitinho Social Problem-Solving Strategies. (October 2022) - Fischer, Ronald; Karl, Johannes Alfons; Pilati, Ronaldo
We report a longitudinal study of Jeitinho brasileiro (salient cultural characteristic of Brazil) during a period of significant political instability. Previous historical and anthropological sources have pointed to the importance of political instability for cultural changes in behaviors such as jeitinho. We are the first to examine possible individual-level dynamics over time, reporting a 3-year longitudinal study ( N = 205) of two dimensions that differentiate keeping a socially pleasant social climate ( simpatia ) from trickery and breaking social norms. Using longitudinal network analysis, we found (a) reinforcing links between behavioral nodes within each of these two jeitinho clusters over time, (b) few between-cluster links, (c) within-person and between-person components were distinct, and (d) only the between-person structure resembled the overall factor structure. Overall, our data show that cultural behaviors are systematically changing during a political crisis, offering first insights how cultural systems may change via shifts in individual behavior.